Analisis Kinerja Struktur Rangka Beton Bertulang Beraturan Dengan Penambahan Tingkat Menggunakan Struktur Baja - Hilario Alberto Kono; Partogi H Simatupang; Ruslan Ramang (Universitas Nusa Cendana, 2021)
The change of plans on gradually development in building structure can be occur with building operational consideration and owner financial. The purpose of this study was to determine the level of performance of the reinforced concrete frame structure with additional levels using steel structures with different span variations. The results of the analysis are used to determine how big the deviation is between levels and to control the level of structure performance. The conclusion of the study shows that the performance level of the structural model analyzed is immediate occupancy (IO) with a total drift ratio and interstorey drift ratio value of the initial building structure (C3S0) in the x direction and y direction of 0.0004, and for variations in building structure with the addition of levels using steel structures (C3S1, C3S2, C5S1, C5S2, C7S1, C7S2) in the x direction ranging from 0.0005-0.0007 and in the y direction ranging from 0.0010-0.0024.